The Influence Of Competence, Objectivity And Audit Structure On Auditor Performance (Case Study At The Head Office Of The Financial And Development Supervision Agency) - Hurriyaturrohman, Hurriyaturrohman; Indupurnahayu, Indupurnahayu; Ramadhan, Muhammad (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2024)
This study aims to explain the impact of several factors on auditor performance. These factors include: (1) the effect of competence on auditor performance, (2) the effect of objectivity on auditor performance, and (3) the effect of audit structure on auditor performance. The research method used in this study is a quantitative approach. The population of this study consists of auditors who work at the Head Office of the Financial and Development Supervisory Agency. Samples taken as many as 30 respondents using purposive sampling method. The collected data were analyzed using multiple linear regression using IBM SPSS version 25 software. The findings of this study indicate that competence has a positive and significant effect on auditor performance, objectivity also has a positive and significant effect on auditor performance, and audit structure also has a positive and significant effect on auditor performance. significantly to the auditor's performance.